Correlating gastric emptying of amphotericin B and paracetamol solid lipid nanoparticles with changes in particle surface chemistry - Amekyeh, Hilda; Billa, Nashiru; Roberts, Clive J. (Elsevier, 2017)
Oral delivery of pharmaceuticals requires that they retain their physical and chemical attributes during transit within the gastrointestinal (GI) tract, for the manifestation of desired therapeutic profiles. Solid lipid nanoparticles (SLNs) are used as carriers to improve the absorption of hydrophobic drugs. In this study, we examine the stability of amphotericin B (AmB) and paracetamol (PAR) SLNs in simulated GI fluids during gastric emptying. On contact with the simulated fluids, the particles increased in size due to ingress of the dissolution media into the particles. Simulated gastric emptying revealed that the formulations had mean sizes <350 nm and neutral surface charges, both of which are optimal for intestinal absorption of SLNs. There was ingress of the fluids into the SLNs, followed by diffusion of the dissolved drug, whose rate depended on the solubility of the loaded-drug in the particular medium. Time-of-flight secondary ion mass spectrometry analyses indicated that drug loading followed the core-shell model and that the AmB SLNs have a more drug-enriched core than the PAR SLNs do. The AmB SLNs are therefore a very suitable carrier of AmB for oral delivery. The stability of the SLNs in the simulated GI media indicates their suitability for oral delivery.